2015
DOI: 10.1055/s-0035-1544232
|View full text |Cite
|
Sign up to set email alerts
|

Short-term and Long-term Postoperative Safety of Off-Pump versus On-Pump Coronary Artery Bypass Grafting for Coronary Heart Disease: A Meta-analysis for Randomized Controlled Trials

Abstract: Short-term postoperative safety was similar between off-pump and on-pump CABG. A high revascularization rate was the drawback of off-pump CABG for CHD patients in long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
(83 reference statements)
2
10
0
Order By: Relevance
“…It can be done with the use of extracorporeal circulation or without ("on-pump" or "off-pump"), with small differences in the efficiency of these two methods. 7,8) Our research included patients who were operated by "on-pump" method, which is today represented in the world in over 80% of procedures, 9) and which still in certain categories of patients shows better results. 10) We have already reported on QOL improvement that patients have 6 months after CABG.…”
Section: Discussionmentioning
confidence: 99%
“…It can be done with the use of extracorporeal circulation or without ("on-pump" or "off-pump"), with small differences in the efficiency of these two methods. 7,8) Our research included patients who were operated by "on-pump" method, which is today represented in the world in over 80% of procedures, 9) and which still in certain categories of patients shows better results. 10) We have already reported on QOL improvement that patients have 6 months after CABG.…”
Section: Discussionmentioning
confidence: 99%
“…Some caution might therefore be advised in the interpretation of the results. Nevertheless, the synthesised results showed that there was no difference in the incidence of mortality, myocardial infarction and stroke between the two groups; however, there was a significantly higher rate of revascularisation in the off pump group (12). It is noteworthy that the single 6 months follow up and the two 1-year follow ups discussed in this metaanalysis were from three of the large RCTs mentioned above (CORONARY, DOORS and GOPCABE) (12).…”
mentioning
confidence: 83%
“…Nevertheless, the synthesised results showed that there was no difference in the incidence of mortality, myocardial infarction and stroke between the two groups; however, there was a significantly higher rate of revascularisation in the off pump group (12). It is noteworthy that the single 6 months follow up and the two 1-year follow ups discussed in this metaanalysis were from three of the large RCTs mentioned above (CORONARY, DOORS and GOPCABE) (12). It should also be noted that Luo et al missed at least one study, namely that of Angelini et al who pooled the follow up (1-3 years) results of two of their RCTs (13).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…It is worth mentioning two further meta-analyses in this section, because they attempted to investigate longer-term outcomes, although longerterm in these cases means either 1-year of followup or anything over 6 months. One of these studies used inclusion criteria, which excluded participants with a mean age <60 years (13). As a consequence, only 4 so-called long term studies were included [GOPCABE (1-year) (12); DOORS (6-months) (10); CORONARY (1-year) (14) and Møller (3-year) (15)] and significant RCTs including Angelini et al (4) were missed.…”
Section: Evidence From Meta-analysesmentioning
confidence: 99%